An upstream Hfq binding site in the fhlA mRNA leader region facilitates the OxyS-fhlA interaction. - Nilshad N Salim; Andrew L Feig (PLoS ONE)
Background To survive, bacteria must be able to adapt to environmental stresses. Small regulatory RNAs have been implicated as intermediates in a variety of stress-response pathways allowing dynamic gene regulation. The RNA binding protein Hfq facilitates this process in many cases, helping sRNAs base pair with their target mRNAs and initiate gene regulation. Although Hfq has been identified as a critical component in many RNPs, the manner by which Hfq controls these interactions is not known. Methodology/principal findings To test the requirement of Hfq in these mRNA-sRNA complexes, the OxyS-fhlA system was used as a model. OxyS is induced in response to oxidative stress and down regulates the translation of fhlA, a gene encoding a transcriptional activator for formate metabolism. Biophysical characterization of this system previously used a minimal construct of the fhlA mRNA which inadvertently removed a critical element within the leader sequence of this mRNA that effected thermodynamics and kinetics for the interaction with Hfq. Conclusions/significance Herein, we report thermodynamic, kinetic and structural mapping studies during binary and ternary complex formation between Hfq, OxyS and fhlA mRNA. Hfq binds fhlA mRNA using both the proximal and distal surfaces and stimulates association kinetics between the sRNA and mRNA but remains bound to fhlA forming a ternary complex. The upstream Hfq binding element within fhlA is similar to (ARN)(x) elements recently identified in other mRNAs regulated by Hfq. This work leads to a kinetic model for the dynamics of these complexes and the regulation of gene expression by bacterial sRNAs.